Ecophysiology of seed germination in Digitaria insularis ((L.) Fedde) - Mendonça, Giovana Soares de [UNESP]; Martins, Cibele Chalita [UNESP]; Martins, Dagoberto [UNESP]; Costa, Neumárcio Vilanova da (Universidade Federal do Ceará, 2014)
The invasive behaviour of sourgrass (Digitaria insularis) in cultivated areas is due to its strategy of aggressive regeneration, which is based on seed germination. Knowledge of the physiological ecology of this species can contribute to the development of management and control strategies. The aim of this research was to understand the effects of provenance, temperature and light on the germination of sourgrass seeds collected in the Brazilian state of São Paulo in the cities of Americana, Botucatu and São José do Rio Preto and in the state of Paraná in the city of São Miguel do Iguaçu. The seeds were left to germinate at temperatures of 15, 25, 35 and 45 °C, both with and without light. The number of normal seedlings was recorded daily from seven to 60 days. After this period, the seeds together with substrate, were transferred to 25 ºC with light, and a daily count was made for all treatments until the end of germination (75 days after sowing). The seeds of D. insularis are positively photoblastic. Seed germination in this species depends on provenance. A temperature of 4 5 °C for germination is lethal to the seeds. The temperature of 35 °C in the presence of light is the most favourable condition for seed germination.

O comportamento invasivo do capim-amargoso (Digitaria insularis) em áreas de cultivo deve-se à sua estratégia de regeneração agressiva, que está alicerçada na germinação das sementes. O conhecimento da ecofisiologia dessa espécie pode contribuir para o desenvolvimento de estratégias de manejo e controle. Objetivou-se com a presente pesquisa conhecer o efeito de diferentes procedências, temperaturas e luz na germinação de sementes de capim-amargoso. As sementes foram coletadas no Estado de São Paulo nas cidades de Americana, Botucatu e São José do Rio Preto e no Estado do Paraná na cidade de São Miguel do Iguaçu e, colocadas para germinar em temperaturas de 15; 25; 35 e 45 °C, com e sem luz. Foram contabilizadas diariamente as plântulas normais de sete a 60 dias. Após esse período, os substratos com sementes foram transferidos para 25 ºC na presença de luz realizando-se contagem diária até que a germinação cessasse em todos os tratamentos (75 dias após a semeadura). As sementes de D. insularis são fotoblásticas positivas. A germinação das sementes desta espécie depende da procedência. A temperatura de 45 ºC para a germinação é letal às sementes. A temperatura de 35 ºC combinada com luz é a condição mais favorável para a germinação das sementes.
Ecofisiologia da germinação de sementes de Digitaria insularis ((L.) Fedde)
Keywords: Capim-amargoso; Fisiologia vegetal; Procedência; Luz; Temperatura; Sourgrass; Plant physiology; Provenance; Light; Temperature